Plantago lagopus extract as a green fungicide induces systemic resistance against Rhizoctonia root rot disease in tomato plants - Behiry, Said I.; Al-Askar, Abdulaziz A.; Soliman, Seham A.; Alotibi, Fatimah O.; Basile, Adriana; Abdelkhalek, Ahmed; Elsharkawy, Mohsen Mohamed; Salem, Mohamed Z. M.; Hafez, Elsayed E.; Heflish, Ahmed A. (Frontiers in Plant Science, 2022)
The extensive use of chemical control agents and fungicides usually results in many human health and environmental hazards. The use of plant extracts as natural substances represents a dual key for the environment and sustainable food production, as it reduces the input of synthetic pesticides into the environment and/or controls plant pathogens. In the current study, the ethanolic extract of Plantago lagopus was characterized and evaluated for its protective and curative efficacy against Rhizoctonia solani in tomato plants under greenhouse conditions for the first time. The results showed that P. lagopus extract (10 μg/mL) completely inhibited R. solani mycelial growth in vitro. At 20 days post fungal inoculation, the results demonstrated that using P. lagopus extract (100 µg/mL) in vivo enhanced tomato plant growth by significantly increasing shoot and root parameters in protective and curative treatments. Furthermore, the protective and curative treatments significantly reduced the disease index by 18.66% and 38.66%, respectively. Induction of systemic resistance with up-regulation of PR-1 and PR-2 and a significant increase in the transcriptional levels of PR-3 and CHS in all P. lagopus extract-treated tomato plants were reported compared to untreated plants. HPLC analysis showed that the most common polyphenolic components detected in P. lagopus extract were rutin (74206.3 mg/kg), naringenin (2388.74 mg/kg), quercetin (1249.13 mg/kg), p-hydroxybenzoic acid (1035.87 mg/kg), ellagic acid (798.47 mg/kg), vanillic acid (752.55 mg/kg), catechol (648.89 mg/kg), cinnamic acid (332.51 mg/kg), ferulic acid (296.32 mg/kg), benzoic acid (295.95 mg/kg) and chlorogenic acid (116.63 mg/kg). Our study is the first to show that P. lagopus extract can help plants fight off R. solani fungal infection. Furthermore, the findings imply that the P. lagopus extract as a natural biocontrol agent could be used as a sustainable control strategy to manage plant fungal diseases.